Spanish background on public and private schools ¿Conflict or complementarity? - Bienvenido Martín Fraile (FahrenHouse, 2008)
Through this paper we try to seek the on-going debates in which public and private schools have been involved across the Spanish history. The fighting among laicity and religious matters at educational field entails a common issue across the latest two hundred years of scholar history. In spite of the advances of seculariza- tion happened during the last decades this is an unfinished and not solved question. The controversial point lies on the freedom of education principle. Finally, the paper also emphasize the important role that has played the private education in schooling processes. Key words: Public schools, Private schools, History of education.